ANALISIS KENAKALAN SISWA SMK DAN KETERKAITANNYA DENGAN KONSEP DIRI: PERSPEKTIF TEORI CARL ROGERS - Tuti Azizah; Rafida Rafida (Jurnal Pendidikan Sultan Agung, 2026)
This study aims to analyze the delinquent behavior of vocational high school (SMK) students through a literature review approach by linking it to the concept of self-concept according to Carl Rogers. Based on the humanistic psychology perspective, self-concept is understood as an internal perceptual structure that influences how individuals understand themselves and behave in a social context. The literature review shows that SMK student delinquency is often triggered by internal factors (emotional instability, low self-esteem, distorted self-concept) and external factors (permissive school environment, family parenting patterns, and peer group dynamics). Previous studies also confirm that a positive self-concept plays a protective role in preventing adolescents from engaging in deviant behavior. The findings of this study produce several practical recommendations for vocational school teachers, including: (1) developing a student-centered learning approach to strengthen a positive self-concept; (2) implementing basic counseling based on Rogers' principle of unconditional positive regard to build a supportive teacher-student relationship; (3) conducting preventive behavior monitoring through collaboration with homeroom teachers and school counselors; and (4) building a school climate conducive to adolescent psychosocial development. The implications of this study emphasize the importance of the role of teachers as facilitators of personality development, not merely as conveyors of knowledge.